Evaluasi Minat Wisatawan Berbasis Persepsi Gender Pada Kayutangan Heritage Melalui Analisis Sentimen Pada Google Point Of Interest" - Shalsabilla, Syahira Aulia; Poerwati, Titik; Hamidah Imaduddina, Annisaa; Afrianto, Firman (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
This study evaluates tourist interest at the Kayutangan Heritage area in Malang City based on gender perceptions through sentiment analysis of reviews on Google Point of Interest (POI). The research employs a big data approach by collecting reviews from Google Maps using web scraping techniques and processing them with the TextBlob algorithm to classify sentiments into positive, neutral, and negative categories. A total of 2,198 reviews were analyzed from six food and beverage (F&B) points across six spatial clusters of the Kayutangan Heritage area. The data were divided into two datasets—overall and gender-labeled—to identify sentiment tendencies among male and female tourists. The results indicate that female tourists tend to prefer Café Lafayette (Cluster 1.A), which offers women-friendly facilities such as separate restrooms and prayer rooms, with a positive sentiment of 67.6%. Meanwhile, male tourists are more interested in Kedai Sedjiwa (Cluster 2.B), which provides a clean environment, modern architecture, and a comfortable ambiance, generating 77.1% positive sentiment. The findings support Chebli et al.’s (2020) model of gender-based tourist preferences, demonstrating that men and women prioritize different elements of a destination. This study contributes to the development of gender-inclusive tourism strategies and data-driven management for heritage destinations.